Tumor-associated macrophages and CD8+ T cells: dual players in the pathogenesis of HBV-related HCC - Khan, Muhammad Naveed; Mao, Binli; Hu, Juan; Shi, Mengjia; Wang, Shunyao; Rehman, Adeel Ur; Li, Xiaosong (Frontiers in Immunology, 2024)
HBV infection is a key risk factor for the development and progression of hepatocellular carcinoma (HCC), a highly invasive tumor, and is characterized by its persistent immunosuppressive microenvironment. This review provides an in-depth analysis of HBV-related HCC and explores the interactions between neutrophils, natural killer cells, and dendritic cells, examining their roles in regulating tumor-associated macrophages and CD8+ T cells and shaping the tumor microenvironment. Two critical players in the immunosuppressive milieu of HBV-related HCC are CD8+ T cells and tumor-associated macrophages (TAMs). The study explores how TAMs, initially recruited to combat infection, transform, adopting a tumor-promoting phenotype, turning against the body, promoting tumor cell proliferation, suppressing anti-tumor immunity, and assisting in the spread of cancer. Meanwhile, CD8+ T cells, crucial for controlling HBV infection, become dysfunctional and exhausted in response to persistent chronic viral inflammation. The review then dissects how TAMs manipulate this immune response, further depleting CD8+ T cell functions through mechanisms like arginine deprivation and creating hypoxic environments that lead to exhaustion. Finally, it explores the challenges and promising therapeutic avenues that target TAMs and CD8+ T cells, either separately or in combination with antiviral therapy and personalized medicine approaches, offering hope for improved outcomes in HBV-related HCC.